Eksegese Keluaran 20 : 3 Tentang “ Jangan ada padamu allah lain di hadapanKu,”suatu Telaah Kritis Terjemahan, terhadap Alkitab Terjemahan Baru. - Ranti, Ezra Gabriel Nehemia (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2023)
This text is very important to examine, so that its meaning is not practically understood, so that it can be trapped in a false understanding. In Hebrew, there are two types of prohibitions: temporary prohibitions that are often translated with the word 'do not' and absolute or permanent, normative prohibitions that are often translated with the word 'shall not'. In the New Living Translation, the form of prohibition used is the word 'do not'. The use of this form of prohibition in the New Living Translation tends not to indicate a normative meaning, which can lead to misunderstanding if read practically. Therefore, the author considers it important to be able to criticize this translation by describing the meaning of its exegesis, so that it can be interpreted as it should be, understood correctly and can be applied in the life of believers at all times. To elaborate on the author's intention above, the author examines this part of the text by using the Biblical research method with the principle of Grammatical Hermeneutics in order to obtain the true meaning of this text, with a descriptive system through Library Research. So that it can answer the problem of practical understanding. It is hoped that the results of this study can provide meaningful input for the proper translation of this text so that it is easier to understand and reflect in the life of faith for believers, as well as contributing good and correct theological knowledge of this text.